Orientation-controlled crystallization of γ-glycine films with enhanced piezoelectricity. Issue 36 (16th August 2022) - Sui, Jiajie; Li, Jun; Gu, Long; Schmidt, Connor A.; Zhang, Ziyi; Shao, Yan; Gazit, Ehud; Gilbert, Pupa U. P. A.; Wang, Xudong
Abstract : Orientation of glycine crystals are tuned by the surface curvature at nucleation site with enhanced piezoelectricity in self-assembled glycine–PVA films. Abstract : Glycine, the simplest amino acid, is considered a promising functional biomaterial owing to its excellent biocompatibility and strong out-of-plane piezoelectricity. Practical applications require glycine films to be manufactured with their strong piezoelectric polar 〈001〉 direction aligned with the film thickness. Based on the recently-developed solidification approach of a polyvinyl alcohol (PVA) and glycine aqueous solution, in this work, we demonstrate that the crystal orientation of the as-synthesized film is determined by the orientation of glycine crystal nuclei. By controlling the local nucleation kinetics via surface curvature tuning, we shifted the nucleation site from the edge to the middle of the liquid film, and thereby aligned the 〈001〉 direction vertically. As a result, the PVA–glycine–PVA sandwich film exhibits the highest aver-age piezoelectric coefficient d 33 of 6.13 ± 1.13 pC N −1 . This work demonstrates a promising kinetic approach to achieve crystallization and property control in a scalable biocrystal manufacturing process.